Metodologiczne pułapki badania wypowiedzi ustnych uczniów na lekcji jęz yka obcego - Kucharczyk, Radosław (Neofilolog, 2010)
The purpose of this paper is to present a gap between theory and practice in foreign language methodology. The case is research which has been conducted in order to investigate the increase of pragmatic competence in oral expression in secondary school students of a French as a foreign language class. The basis for choice of research methods, as well as difficulties encountered by the researcher while conducting the research project at school, are described.